Modulating eating behavior with transcranial direct current stimulation (tDCS): A systematic literature review on the impact of eating behavior traits. (17th November 2021) - Beaumont, Jordan D.; Smith, Natalie C.; Starr, David; Davis, Danielle; Dalton, Michelle; Nowicky, Alexander; Russell, Mark; Barwood, Martin J.
Summary: Transcranial direct current stimulation (tDCS) is becoming an increasingly popular technique for altering eating behaviors. Recent research suggests a possible eating behavior trait‐dependent effect of tDCS. However, studies recruit participant populations with heterogeneous trait characteristics, including "healthy" individuals who do not present with eating behavior traits suggesting susceptibility to overconsumption. The present review considers the effects of tDCS across eating‐related measures and explores whether a trait‐dependent effect is evident across the literature. A literature search identified 28 articles using sham‐controlled tDCS to modify eating‐related measures. Random effects meta‐analyses were performed, with subgroup analyses to identify differences between "healthy" and trait groups. Trivial overall effects ( g = −0.12 to 0.09) of active versus sham tDCS were found. Subgroup analyses showed a more consistent effect for trait groups, with small and moderate effect size ( g = −1.03 to 0.60), suggesting tDCS is dependent on participants' eating behavior traits. Larger effect sizes were found for those displaying traits associated with study outcomes (e.g., heightened food cravings). "Healthy" individuals appear to be unresponsive to stimulation. Based on this meta data, future work should recruit those with eating behavior trait susceptibilities to overconsumption, focusing on those who present with traits associated with the outcome of interest.